A NEW MIXED SURGICAL TREATMENT FOR GRADES III AND IV HEMORRHOIDS: MODIFIED SELECTIVE HEMORRHOIDECTOMY COMBINED WITH COMPLETE ANAL EPITHELIAL RETENTION - HUANG,Hua (2021)
ABSTRACT Background: Varicose veins appear above and below the dentate line in mixed hemorrhoids, which seriously affects anal function and quality of life. Aim: To propose an improvement in tissue-selecting therapy repair of anal pad combined with complete anal canal epithelial retention comparing with Milligan-Morgan surgery. Methods: A prospective randomized controlled study was designed enrolling 200 patients with grade III and IV hemorrhoids. They were divided into control and observation groups. The control received Milligan-Morgan surgery, and the observation the modified tissue-selecting therapy stapler combined with complete anal canal preservation surgery. All patients were followed for six months to evaluate the treatment differences. Results: In final, control group included 82 and observation 87. The average operation time of the control group was significantly lower than that of the observation, while the bleeding volume was significantly lower in control group. The control group VAS score was 3 (1, 4), and observation 4 (2, 5). There was no significant difference in the incidence of urinary retention, bleeding and wound margin edema after surgery at one month postoperatively. Digital incidence of anal stenosis in the observation group was significantly lower than in control; the same occurred with residual anal margins. The postoperative anal canal diameter was significantly larger than the control group. Wexner anal incontinence score showed that no anal incontinence occurred in both groups, and the control group scored was significantly higher than observation. In final six months follow-up, the observation group did not experience any relapse and four cases were found among controls. The treatment satisfaction of the observation group was better. Conclusions: In grades III and IV hemorrhoids, modified tissue-selecting therapy combined with complete anal canal preservation had better prognosis and treatment satisfaction than Milligan-Morgan procedure, and it is a new surgical method for patients with advanced mixed hemorrhoids.